2006
DOI: 10.1183/09031936.00036006
|View full text |Cite
|
Sign up to set email alerts
|

Severe airflow obstruction and eosinophilic lung disease after Stevens–Johnson syndrome

Abstract: Respiratory involvement is a frequent complication of Stevens-Johnson syndrome (SJS). However, there are very few convincing reports of persistent pulmonary sequelae, as demonstrated by spirometry, radiology and pathology.The current study presents a case of a 13-yr-old female with T-cell acute lymphocytic leukaemia who developed persistent, severe, obstructive lung disease following an episode of SJS.A lung biopsy demonstrated bronchiolar submucosal fibrosis consistent with constrictive bronchiolitis, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In survivors, late pulmonary sequelae, including interstitial lung disease, respiratory tract obstruction, bronchiectasis, bronchitis and bronchiolitis obliterans (BO), have all been observed, with the latter being the most commonly reported (Table ) . BO is a consequence of airway epithelial injury with subsequent epithelial regeneration and scarring.…”
Section: Pulmonary Sequelaementioning
confidence: 99%
“…In survivors, late pulmonary sequelae, including interstitial lung disease, respiratory tract obstruction, bronchiectasis, bronchitis and bronchiolitis obliterans (BO), have all been observed, with the latter being the most commonly reported (Table ) . BO is a consequence of airway epithelial injury with subsequent epithelial regeneration and scarring.…”
Section: Pulmonary Sequelaementioning
confidence: 99%
“…Chronic pulmonary complications resulting from TEN and SJS are rare. According to previous studies published in English, 22 patients who suffered from chronic pulmonary diseases following TEN/SJS were identified, including the present case (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The age of patients ranged between 2 and 52 years, and there were 10 male and 12 female patients (Table I).…”
Section: Discussionmentioning
confidence: 94%
“…Finally, production of growth factors such as TGF-β which promote fibroblast proliferation may result in fibrosis at late phase of BO formation. In addition, Shah et al [8] reported that a case of constrictive BO and eosinophilic micro-abscesses after SJS. It is known that eosinophils are important sources of a variety of pro-fibrogenic mediators such as TGF-α [12], TGF-β [13], vascular endothelial growth factor [14], and interleukin-13 [15].…”
Section: Discussionmentioning
confidence: 99%